Towards open building system in housing: A joint-venture of building technology for manufactured home in Malaysia - Ismail, Zulkefle; Abdul Rahim, Asiah; Abu Eusuf, Mohammad (2010)
Previous studies show that the implementation of Industrialized Building System (IBS) in Malaysia gives significant benefits the construction industry by reducing the site labour, clean site and fast construction. However, the qualities of the local IBS products are still being argued. Manufactured home constructed in developed countries appears to have cheaper construction cost compare to conventional method. The paper describes the idea of JointVenture (JV) project to improve quality of IBS product for manufactured homes in Malaysia. This technology of construction will be applied in this context. The study explores the possibility of introducing the prefabricated volumetric component to merge with the existing paneling of IBS which are available in Malaysia. The innovations which are emerging locally and from overseas would make these potential extensions possible. The construction industry should operate in a „zero waste and zero defect‟ environment as given in the Egan Report (1998) for improving quality and speed of construction. Therefore, the study on technology transfer and implementation of manufactured home in European countries and Japan were explored. The opportunities of implementing JV for manufactured homes were not only sharing knowledge and innovative ideas but also for the success of sustainable construction. This could help the construction industry in Malaysia in promoting Green construction towards open system and sustainable development in housing. The methods of data collection include questionnaire, semi-structured interview and observation are carried out in United Kingdom. In conclusion, this study provide the possibility of getting more available systems in prefabrication technology of housing to be merged as a JV project for manufactured home in Malaysia.